How to safeguard the continuous renal replacement therapy circuit: a narrative review - Hu, Chaomin; Shui, Pengfei; Zhang, Bo; Xu, Xin; Wang, Zhengquan; Wang, Bin; Yang, Jie; Xiang, Yang; Zhang, Jun; Ni, Hongying; Hong, Yucai; Zhang, Zhongheng (Frontiers in Medicine, 2024)
The high prevalence of Acute Kidney Injury (AKI) in ICU patients emphasizes the need to understand factors influencing Continuous Renal Replacement Therapy (CRRT) circuit lifespan for optimal outcomes. This review examines key pharmacological interventions — citrate (especially in regional citrate anticoagulation), unfractionated heparin (UFH), low molecular weight heparin (LMWH), and nafamostat mesylate (NM) — and their effects on filter longevity. Citrate shows efficacy with lower bleeding risks, while UFH remains cost-effective, particularly in COVID-19 cases. LMWH is effective but associated with higher bleeding risks. NM is promising for high-bleeding risk scenarios. The review advocates for non-tunneled, non-cuffed temporary catheters, especially bedside-inserted ones, and discusses advantages of surface-modified dual-lumen catheters. Material composition, such as polysulfone membranes, impacts filter lifespan. Treatment modality choice (CVVHD or CVVHDF), effluent volume, blood flow rates, and downtime management are critical in prolonging filter longevity in CRRT. Patient-specific conditions and early mobilization during CRRT contribute to extending filter lifespan. In conclusion, this review offers insights into factors influencing CRRT circuit longevity, supporting evidence-based practices and suggesting further multicenter studies to guide ICU clinical decisions.